Conjunctival cytology in patients treated for ocular infectious diseases - Sh. A. Dzhamalova; N. R. Yangieva; Z. Kh. Kuryazova (Ukrainian Society of Ophthalmologists, 2021)
Background: Anti-inflammatory therapy is a mainstay of treatment for patients with ocular inflammatory disorders. Although glucocorticosteroids (GCS) demonstrate a potent anti-inflammatory and anti-allergic effect, treatment with GCS is associated with a risk of serious side effects. Non-steroidal anti-inflammatory agents (NSAIDs) possess somewhat lower anti-inflammatory activity compared to GCS, and their development and incorporation into clinical eye care practice seem reasonable. Purpose: To assess the efficacy of a 0.5% benzketosone ointment, a novel topical ocular medication manufactured in Uzbekistan, in the treatment of infectious conjunctivitis and blepharitis. Material and Methods: One hundred and thirty-one patients (175 eyes; 64 men and 67 women) were included in this study to assess the efficacy of treatment with 0.5% benzketosone ointment (Certificate №06-07) for ocular inflammatory disorders. Patients of the control group received the conventional therapy, whereas those of the experimental group received 0.5% benzketosone ointment in addition to the conventional therapy. A modified impression cytology technique was used to monitor the therapeutic effect. Results: Modified impression cytology showed that the incorporation of benzketosone ointment in the conventional treatment for conjunctivitis or blepharitis resulted in a substantial decrease in exudation and cell proliferation, which was manifested by a decrease in numbers of basophils and eosinophils, restoration of epithelial cell structure and earlier normalization of mean nucleocytoplasmic ratio values and earlier reduction in tissue and protein detritus in conjunctival specimens of the experimental group compared to controls. Conclusion: Modified impression cytology provided evidence that the incorporation of benzketosone ointment in the conventional treatment for conjunctivitis or blepharitis improved regenerative activity, metabolic processes and symptoms of ocular inflammation.